Characteristics of Different Chitosan Types on κ-Carrageenan Polyelectrolyte Complex (PEC) Bioplastics as Food Packaging - Puteri, Dhena Celia Haryadi; Alamsjah, Mochammad Amin; Sulmartiwi, Laksmi (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlights Research 1. This study investigates the impact of incorporating chitosan from different sources (shrimp, crab, and fish scales) with varying molecular weights on the mechanical characteristics of bioplastics used for food packaging. 2. The present study aims to optimize the volume ratio of κ-carrageenan and chitosan to form stable polyelectrolyte complexes (PECs) for bioplastic production. 3. This study evaluates the quality of tilapia fillets wrapped with κ-carrageenan and chitosan PEC bioplastics after 24 h storage. 4. The present study investigates the reaction mechanism involved in the formation of polyelectrolyte complexes between κ-carrageenan and chitosan for bioplastic production. Abstract Bioplastic represents an eco-friendly alternative to synthetic plastic and can be derived from natural polysaccharides like carrageenan. κ-carrageenan is noted for its gel-forming properties, making it a common raw material for bioplastics. Mechanical properties values of κ-carrageenan bioplastics are usually below standard. The addition of materials such as chitosan can enhance those properties. Chitosan-carrageenan can form polyelectrolyte complexe (PEC) through electrostatic interactions without toxic crosslinking agents. Polymer’s molecular weight is a crucial factor influencing PEC formation. Chitosan's molecular weight varies based on the raw material and extraction process. This study aims to identify the most suitable type of chitosan for food packaging bioplastics using polyelectrolyte complex (PEC) method. Three types of commercial chitosan with different molecular weights were evaluated (shrimp, crab, and fish scale chitosan). Japanese Industrial Standards (JIS) were used for characterization assessment of bioplastics such as thickness, tensile strength, water resistance, water vapor transmission, and biodegradation rate as well as additional tests including Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) analysis, and Total Plate Count (TPC) on fish fillets. The findings indicated that crab chitosan-κ carrageenan PEC bioplastic exhibited optimal results with a thickness of 0.178 mm, tensile strength of 18.053 MPa, elongation at break at 211.73%, water resistance of 63.94%, water vapor transmission (WVT) of 0,001456 g/m2/day, biodegradation rate of 3.358% over 7 days, and the lowest TPC in fish fillets after 24 h, increasing from 4.39 log CFU/g to 7.45 log CFU/g. Molecular weight of chitosan was shown to significantly influence the PEC bioplastics’ characteristics.